Organizational Culture on Lecturer Performance: Organizational Commitment as an Intervening Variable - Nugroho, Moch Indah Hastomo; Soelistya, Djoko; Wijayanti, Tri Cicik; Agustina, Heni (Budapest International Research and Critics University, 2021)
This research was conducted in one of the universities (organizations) in Gresik, which, in the university environment, the performance of lecturers is very important in improving the quality of higher education. The problems caused are still found in the performance of lecturers whose achievements are below the standards given by universities, which are suspected of having the culture and commitment of University given to the performance of lecturers that are still less than optimal. This research mean for analyze and find solutions to problems caused by organizational culture and commitment. This study uses a quantitative method, where the respondents are 95 students from the questionnaire sample by the college students, while the data analysis uses the Smart Partial Least Square (PLS) methods. This research show that University Culture and Commitment having a direct and significant impact on lecturer performance, but University Culture has an effect but not significantly on Lecturer Performance if through University Commitment. Therefore, policies, policies and organizational culture provided by universities should also pay attention to the interests expected by lecturers.